The Urgency Of Imposing The Death Penalty On Drug Dealers From A Human Rights Perspective - Bobby Satria Ermando; Zainal Abidin Pakpahan; Toni Toni (CV. AFDIFAL MAJU BERKAH, 2025)
This study uses a normative legal research method. Normative legal research is examining law from an internal perspective with the object of research being legal norms. This study aims to determine the Urgency of Imposing the Death Penalty on Narcotics Dealers Reviewed from a Human Rights Perspective. Discussion Results: The death penalty is one of the main punishments regulated in Article 10 of the Criminal Code. Where, the death penalty is carried out by shooting the perpetrator dead as regulated in the law. The death penalty is a form of accountability for unlawful acts and this punishment is the highest punishment of all existing punishments and is regulated in the Criminal Code. The death penalty for drug dealers is something that must be done and expedited, because the circulation of narcotics is currently increasingly rampant and the impacts it causes greatly affect the lives of the nation's next generation, as well as security and order in the nation and state today and in the future. The consideration to impose the death penalty on drug dealers is more directed towards providing a deterrent effect on the perpetrators as well as law enforcement to create a sense of justice in society. The death penalty imposed under Indonesian law still has pros and cons in some circles of society and legal observers. That the death penalty is a violation of the Human Rights to life, because basically death belongs only to God Almighty. The death penalty when associated with the Human Rights Law, then clearly violates what is formulated in the Human Rights Law Articles 4 and 9. However, in contrast to what is stated in Articles 70 and 73, that there are restrictions set by law as long as the freedom to live does not violate the provisions set by law, such as violating public order, morality, morals, or the interests of the nation. While the criminal acts committed by drug dealers have clearly violated the provisions in question, the death penalty is actually a punishment that clearly does not violate the Human Rights Law.